Systematic Review and Meta-analyses - InaACC, InaACC (The Indonesian Heart Association, 2024)
Systematic Review and Meta-analyses - Abstracts of the 6th Indonesian Intensive & Acute Cardiovascular Care Meeting (InaACC) 2024